Pengaruh Berbagai Merek Pupuk Organik terhadap Pertumbuhan dan Produksi Pakcoy pada Lahan Kering Masam - Wahyu Aji Saputra; Fadly Hairannoor Yusran; Zuraida Titin Mariana (Agroekotek View, 2022)
This research objective was to obtain the best organic feltilizer brand for the growth and production of bok choy in acid dryland. This research was conducted in a greenhouse owned by Departement of Agricultural Cultivation, Faculty of Agricultural, Lambung Mangkurat University, Banjarbaru. This research was conducted from February 2020 - April 2020. Factorial completely randomized design was applied with 10 t ha-1 for all brands. The treatments were: P0 = Control, P1 = 10 t ha-1 2- Tia-Agri, P2 = 10 t ha-1 Sunflower, P3 = 10 t ha-1 Supernasa, and P4 = 10 t ha-1 Evergreen with five replicates.  The results showed that organic fertilizer brands affected growth and production of bok choy.  The best dose was Evergreen with 10 t ha-1 (P4).